Estudio del proceso de conservación de paiche (Arapaimas gigas) aplicando distintos aceites de origen vegetal: Sacha inchi (Plukenetia volubilis), ajonjolí (Sesamun indicum), maní (Arachis hypogaea - Carrasco Mendoza, Rosita Nataly (2021)
The objective of this research was to study the effect of Sacha inchi (Plukenetia volubilis), Sesame (Sesamun indicum) and Peanut (Arachis hypogaea) oils in the preservation process of Paiche (Arapaimas gigas), so analyses were carried out on the fatty profile as well as the physical-chemical and bromatological properties of the types of oils, the types of cuts, salami and canned paiche mojama; In addition, a material balance was carried out for each product to determine the yield of the oils and a sensory evaluation to determine their acceptability. The research was carried out by preparing the products to be analyzed. To determine the difference between the properties of the fatty acid profile, physical-chemical and bromatological properties, an A*B factorial design with three replications was used for the preparation of a salami-type sausage and a canned mojama, the study factors being: Factor A: Types of oils (sacha inchi, sesame and peanut oil), Factor B: Types of cut (loin and belly). To establish the effects between treatment levels, Tukey's significance test was applied (p<0.05), being analyzed by means of the statistical packages "Statgraphics" and "Statistica". Therefore, the results obtained were: as for the types of oils, sacha inchi oil contains the best results in saturated fatty acids, while, in the types of cut, the belly presents the best results for monounsaturated and polyunsaturated acids. As for the physicochemical and bromatological results of salami and mojama preserves, better results were obtained where sacha inchi oil and sesame oil were used with loin cut, these treatments being the most acceptable in terms of sensory evaluation results. Key words: Paiche, mojama, salami, fat profile, sacha inchi, sesame, peanut.